2020
DOI: 10.5688/ajpe7453
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Ability to Identify the Steps of the Pharmacists’ Patient Care Process During IPPE

Abstract: Objective. To determine the ability of first-year Doctor of Pharmacy (PharmD) students to describe patient care activities performed by pharmacists and accurately associate those activities with the five core steps of the Pharmacists' Patient Care Process (PPCP). Methods. First-year student pharmacists completed introductory practice experiences at ambulatory and institutional pharmacies. Students' ability to describe activities that occurred in these settings and align them with the five core steps (collect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The importance of integrating opportunities for students to apply the PPCP within an institutional or inpatient setting was previously highlighted in a study by Taylor and collegues. 8 This study indicated students often have a harder time identifying activities associated with collection and implementation within inpatient settings and challenged faculty to provide early opportunities for students to apply the PPCP in this setting. 8 The implementation of an OAC education service facilitated this clinical application of didactic skills including the collection of information, creation of therapeutic plans, and implementation of counseling skills in a setting where these opportunities are often lacking compared to ambulatory care settings.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of integrating opportunities for students to apply the PPCP within an institutional or inpatient setting was previously highlighted in a study by Taylor and collegues. 8 This study indicated students often have a harder time identifying activities associated with collection and implementation within inpatient settings and challenged faculty to provide early opportunities for students to apply the PPCP in this setting. 8 The implementation of an OAC education service facilitated this clinical application of didactic skills including the collection of information, creation of therapeutic plans, and implementation of counseling skills in a setting where these opportunities are often lacking compared to ambulatory care settings.…”
Section: Discussionmentioning
confidence: 97%
“…11 Additional studies have described incorporation of PPCP elements within specific coursework or integration within overall curricula. 4,5,10,12,13 Despite the presence of some literature on PPCP incorporation within pharmacy education, studies have been descriptive in nature, focused within one course at one college/school, and have not assessed self-efficacy for individual components of the PPCP. 4,5,10,11 An instrument assessing pharmacy students' self-efficacy in application of the PPCP in practice can be very valuable, especially when utilized with other assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additional studies have described how the PPCP was implemented in an entire pharmacy program 5 and how students' knowledge of the PPCP steps was assessed in a medicinal chemistry course 12 and an IPPE course. 13 There continues to be a need for instruments, with demonstrated validity evidence, that assess students' ability to implement PPCP components, especially as part of advanced pharmacy practice experiences (APPE) and practice readiness assessments. 5 Evaluating student confidence in PPCP is one important component of a global approach to assess students' competency with applying the PPCP.…”
Section: A J P Ementioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Other strategies described in the literature include integration as a curricular thread or within capstone experiences, experiential education, medicinal chemistry, and elective courses. [11][12][13][14][15][16][17] Sorenson and colleagues recently called for the Academy to achieve greater consistency, specificity, and intentionality to teaching the PPCP and to hold itself accountable for preparing graduates who can deliver care with fidelity. 18 Implementation science, the study of methods that influence the integration of evidenced-based interventions into practice, should be leveraged to support these curricular advancement efforts.…”
Section: Introductionmentioning
confidence: 99%